Primary intrapulmonary neurogenic sarcoma with hypertrophic pulmonary osteoarthropathy and asbestosis. Issue 2 (March 1971) - Caves, P. K.; Jacques, J.
Abstract : A case of primary intrapulmonary neurogenic sarcoma with hypertrophic pulmonary osteoarthropathy and asbestosis is described. The essential histological features of this rare tumour are detailed, and the five authentic cases previously reported are reviewed. The pathogenesis of hypertrophic pulmonary osteoarthropathy and its occurrence in this case are discussed. After surgical removal of the tumour recurrence appeared in the chest within six months. It responded poorly to radiotherapy, and death from metastases occurred 16 months after operation.